Changing workplaces in the creative process in creative industries - the case of advertising and music - Growe, Anna; Mager, Christoph (Erdkunde, 2018)
Based on qualitative interviews with senior executives from advertising and the music industry, this paper argues that the organization of creative work is shaped by specific and varying workplace geographies. Work in creative industries can be understood as trans-local processes, making specific use of the physical environment of different workplaces and relating workplaces embedded in different logics to one another. The results of the study show that in the creative process, work is carried out in multi-local work arrangements. Starting with the differentiation of team and individual workplaces – derived from the literature dealing with physical environments of creativity supporting workplaces – the paper argues that a relational understanding of multi-local work arrangements should focus on the relation of ‘exposure’ and ‘protection’ provided by each workplace. Exposure and protection are densely interwoven in creative work processes, and mainly refer to the protection of working processes and thoughts from disturbances and a planned exposure to inspirational surroundings that can be realised at specific locations. The paper develops protection and exposure as mutual dependent concepts, influencing the multi-locality of workplaces.